2021
DOI: 10.2166/wst.2021.337
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the comparison of thermally and Fe(II) activated persulfate on sludge dewaterability and disintegration

Abstract: The effects of thermally and Fe(II) activated potassium persulfate (PPS) on sludge dewatering performance were compared systematacially. Sludge dewaterability was monitored by measuring capillary suction time (CST) and sludge specific resistance to filtration (SRF), and the degradation effect was characterized by Chemical oxygen demand (COD), total organic carbon (TOC), ammonia nitrogen (NH4+-N) and extracellular polymeric substances (EPS). The Change of extracellular polymer substance (EPS) including soluble,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This was an additional confirmation that the PDS was easily activated by the nZVI or bimetallic nanoparticles to form sulfate radicals. Analogous results were obtained by Guo et al [32], where Fe(II)-activated PDS caused the conversion of B-EPS to S-EPS.…”
Section: Resultssupporting
confidence: 87%
“…This was an additional confirmation that the PDS was easily activated by the nZVI or bimetallic nanoparticles to form sulfate radicals. Analogous results were obtained by Guo et al [32], where Fe(II)-activated PDS caused the conversion of B-EPS to S-EPS.…”
Section: Resultssupporting
confidence: 87%
“…The most commonly used activation method is Fe 2+ activation, with a standard redox potential of 3.1 V for SO 4− , which exceeds that of the strongly oxidizing -OH and is more stable to oxidizing pollutants, making it more suitable for a wider range of applications. Guo et al [34] uses Fe 2+ activated potassium persulfate (PPS) for sludge treatment. The results showed that the Fe 2+ -activated PPS improved the dewatering performance of the sludge with a lower PPS dosage and a shorter treatment time.…”
Section: Activated Persulfate Conditioningmentioning
confidence: 99%
“…The optimum dosing rates for PPS and Fe 2+ are 0.5 mmol/g and 1.0 mmol/g, respectively CS down to 25.1 s SRF down to 1.75 × 10 8 m/kg [34] Fe 2+ -perthiolate-tannic acid (TA)…”
Section: Pps-fe 2+mentioning
confidence: 99%